Primary Health Care Costs Associated With Trajectories of Physical Activity Over 10 Years. - Codogno, Jamile Sanches [UNESP]; Brown, Wendy J; Turi-Lynch, Bruna Camilo; Morais, Luana Carolina de; Lemes, Ítalo Ribeiro [UNESP]; Monteiro, Henrique Luiz [UNESP]; Mielke, Gregore Iven (Human Kinetics, 2025)
BACKGROUND: The aim of this study was to investigate whether health care costs were influenced by trajectories of physical activity (PA) over a 10-year period. METHODS: Five hundred and forty-one users of primary health care services in Brazil were followed from 2010 to 2020. PA (questionnaire) was assessed every 2 years. The score of PA was used in latent class trajectory models, and 4 trajectories were chosen: (1) low (participants who started and finished the follow-up with the lowest PA values), (2) moderate (participants who started with moderate PA levels and had a slight decrease), (3) decreasing (participants who showed a marked decrease), and (4) high (participants who started and finished with the highest PA levels). Health care costs were retrieved from medical records. Quantile regression was performed to compare costs according to trajectories of PA. RESULTS: Median values of PA scores decreased over time in all groups, but this was more evident in the Decreasing group (54% decline). Costs in each year became more highly skewed over time, with very high maximum costs (approximately US$ 200) noted in the Low and Decreasing groups. Moderate and High groups had lower costs than the Low group in both the median and 90th percentile analyses. Using the median data, compared with costs in the Low group, costs were reduced by 26% and 43% in the Moderate and High groups, respectively. In the 90th percentile, these reductions were 48% and 55%, respectively. CONCLUSION: The achieving and maintaining of moderate or high PA levels over 10 years was associated with significant cost savings.